Garuda Wisnu Kencana: Between Philosophy and Diplomacy - Putu Ratih Kumala Dewi (Future Science, 2022)
The Garuda Wisnu Kencana is a symbol of Balinese culture and art. One of Garuda Wisnu Kencana statues located in the southern part of Bali is the tallest statue in Indonesia, which has become an iconic landmark. Even in Bali, Pakudui village in Gianyar is famous for the art of the Garuda Wisnu Kencana wooden statue. For the Balinese people, Garuda Wisnu is not just a work of art. The philosophical Garuda Wisnu Kencana is inextricably linked to the Balinese way of life. Apart from its close relationship with the local community, at a higher level, namely at the state level, the Garuda Wisnu Kencana statue is used as a diplomatic tool in various events. This article looks at Garuda Wisnu Kencana from a philosophical standpoint, as well as its use in Indonesian diplomacy. This paper uses a qualitative research method. The data used in this paper comes from an interview with Made Ada, a Balinese master wood carver, as well as secondary sources such as government official websites and national media coverage. By using the concept of cultural identity and cultural diplomacy, the author finds that Garuda Wisnu Kencana's philosophy is in line with Indonesian diplomacy and the artwork used as diplomatic tools in several events.